SELF-REPORTED SLEEP DURATION, ANTHROPOMETRIC MEASUREMENTS, RESPIRATORY FUNCTION AND FUNCTIONAL CAPACITY: A CROSS-SECTIONAL STUDY IN THE ELDERLY (CIPEEX, 2022)
AGING INFLUENCES THE NUMBER OF HOURS AND THE QUALITY OF SLEEP, WHICH ARE ASSOCIATED WITH CHANGES IN RESPIRATORY FUNCTION AND AN INCREASE IN OBESITY. OBJECTIVE: TO ASSOCIATE ANTHROPOMETRIC MEASUREMENTS, RESPIRATORY FUNCTION AND SLEEP SCALES WITH THE NUMBER OF HOURS SLEPT. METHODS: EIGHTY-NINE ELDERLY PEOPLE WERE EVALUATED IN A SPECIALIZED CARE HOSPITAL FOR THE ELDERLY. BODY MASS INDEX AND WAIST CIRCUMFERENCE WERE USED TO VERIFY THE PRESENCE OF OVERWEIGHT AND OBESITY. SPIROMETRY EVALUATED LUNG FUNCTION WITH THE FOLLOWING PARAMETERS: PEAK EXPIRATORY FLOW (PEF), FORCED VITAL CAPACITY (FVC) AND FORCED EXPIRATORY VOLUME IN ONE SECOND (FEV1). RESPIRATORY MUSCLE STRENGTH WAS ASSESSED BY MEANS OF MAXIMAL INSPIRATORY PRESSURE (MIP) AND MAXIMAL EXPIRATORY PRESSURE (MEP). THE INSTRUMENTS USED TO ASSESS SLEEP QUALITY WERE THE EPWORTH SLEEPINESS SCALE (ESS) QUESTIONNAIRE AND THE PITTSBURGH SLEEP QUALITY INDEX (PSQI). TO COMPARE THE GROUPS ACCORDING TO THE HOURS OF SLEEP (‰¤6H, BETWEEN 7-9H AND ‰¥10H) THE ONE-WAY ANOVA TEST WITH TUKEY'S POST HOC OR KRUSKAL-WALLIS TEST WITH DUNN'S POST HOC WAS USED. CATEGORICAL VARIABLES WERE ASSOCIATED WITH THE CHI-SQUARE TEST. THE VALUE CONSIDERED FOR P <0.05 AND STATISTICAL PACKAGE FOR SOCIAL SCIENCE SOFTWARE. RESULTS THE MEAN AGE WAS 73.4 YEARS, WITH 57 (64%) WOMEN AND 32 (36%) MEN, THERE WAS NO CORRELATION BETWEEN BMI AND WAIST CIRCUMFERENCE WITH HOURS OF SLEEP. SIGNIFICANCE DIFFERENCE WERE FOUND TO PEF [‰¤6H: 2.1 (0.9) L/S; 7-9H: 3.1 (1.4) L/S; ‰¥10H: 2.4 (1.2) L/S; P*=0.015], FVC [‰¤6H: 1.8 (0.5) L; 7-9H: 2.3 (0.5) L; ‰¥10H: 2.0 (0.7) L; P*=0.003], FEV1 [‰¤6H: 1.4 (0.4) L; 7-9H: 1.8 (0.5) L; ‰¥10H: 1.4 (0.5) L; P*=0.002], MIP [‰¤6H: 39.7 (16.6) CMH2O; 7-9H: 61.6 (31.3) CMH2O; ‰¥10H: 46.5 (23.3) CMH2O; P*=0.020] AND MEP [‰¤6H: 37.6 ( 23.6) CMH2O; 7-9H: 67.7 (34.9) CMH2O; ‰¥10H:  45.2 (20.6) CMH2O; P*=0.001). TH HIGHER VALUES WERE IN THE ELDERLY WHO SLEEP BETWEEN 7-9H WHEN COMPARED TO THOSE WHO SLEEP ‰¤6H. THIS SLEEP DEPRIVATION LEADS TO A PROGRESSIVE REDUCTION IN RESPIRATORY FUNCTION, AND AS CONSEQUENCE, AN INCREASE IN RESTING RESPIRATORY RATE, A DECREASE IN TIDAL VOLUME AND DIAPHRAGMATIC ACTIVITY. THE FEV1/FVC RATIO WAS NOT SIGNIFICANT. THERE WAS A SIGNIFICANT ASSOCIATION BETWEEN BMI, MIP AND MEP WITH HOURS OF SLEEP. CONCLUSION: ELDERLY PEOPLE WHO SLEEP 7-9 HOURS HAVE BETTER RESULTS IN LUNG FUNCTION AND RESPIRATORY MUSCLE STRENGTH.
Keywords: sleep quality; elderly health; respiratory function tests